REFORMULASI SISTEM PERENCANAAN PEMBANGUNAN NASIONAL DENGAN MODEL GBHN (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2017)
One of the results of the amendments to the 1945 Constitution is the loss of GBHN as a guideline or direction for the state in the implementation of national development. This GBHN disappeared as the MPR agency changed its duties as a consequence of changing its institutional position from the highest state institution to being a State high institution. As a substitute for GBHN, Law No. 25 of 2004 regulates the National Development Planning System, which states that the elaboration of the purpose of the establishment of the Republic of Indonesia as contained in the Preamble of the 1945 Constitution, is set forth in the form of RPJP (Long Term Development Plan). The RPJP time scale is 20 years, which is then elaborated in the RPJM (Medium Term Development Plan), namely planning with a 5-year time scale, which contains the president's vision, mission and development program, guided by the RPJP. The problem is when the President takes office the period has expired and the new president has been re-elected, so politically the existence of the law on the National Development planning system is very easily changed, adjusting to the president's elected vision and mission.